Calcium content in post-mining grounds in the Łęknica region = Zawartość form wapnia w gruntach pokopalnianych z rejonu Łęknicy - Drab, Michał; Greinert, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work contains results of a study on the calcium content - subtotal and soluble in 0.1M HCl - in post-mining grounds in Łęknica area. Subtotal content of calcium in the level of forest litter, regardless of the used fertilization during reclamation and the location of the study, was apparently the highest (av. 4108 mgźkg-1).
Keywords: grunty pokopalniane; wapń; Łęknica - okręg; calcium; soil; post mining areas